Site‐specific response patterns, pseudoprogression, and acquired resistance in patients with melanoma treated with ipilimumab combined with anti–PD‐1 therapy. Issue 1 (4th October 2019) - Pires da Silva, Ines; Lo, Serigne; Quek, Camelia; Gonzalez, Maria; Carlino, Matteo S.; Long, Georgina V.; Menzies, Alexander M.
Abstract : Background: Patients with metastatic melanoma have variable responses to combination ipilimumab and nivolumab. The objectives of this study were to examine the patterns of response and survival in patients treated with combination ipilimumab and anti–PD‐1 therapy (IPI + PD1) and to explore the nature of pseudoprogression and acquired resistance. Methods: Patients with metastatic melanoma who received treatment with first‐line IPI + PD1 had all metastases ≥5 mm measured on computed tomography/magnetic resonance imaging studies. The lesional response rate (LRR) and the overall response rate (ORR) were determined according to Response Evaluation Criteria in Solid Tumors, version 1.1. Results: In total, 140 patients who had 833 metastases were studied. The ORR and the overall complete response (CR) rate decreased as tumor burden or the number of metastases increased. Metastases that had a CR (49%) were smaller than metastases without a CR (median, 13 vs 17 mm; P < .0001). Soft‐tissue and lung metastases had the highest LRR (79% and 77%, respectively), whereas liver metastases had the lowest (46%). In multivariate analysis, patients with lung metastases had superior ORR (odds ratio [OR], 2.75; P = .02) and progression‐free survival (hazard ratio [HR], 0.46; P = .02), whereas those with liver metastases had inferior ORR (OR, 0.33; P = .02), progression‐free survival (HR, 4.03; P < .01), and overall survival (HR, 3.17; P = .01). Pseudoprogression occurred in one‐third of patients who had progressive disease as their best response, with an overall survival that was comparable to that of patients without disease progression. Acquired resistance occurred in 12% of responders after a median of 9.6 months, with an overall survival rate of 83% at 1 year from progression. Conclusions: Metastases in different anatomical locations display distinct response patterns and also are associated with overall response and survival with combination immunotherapy. Specific sites of disease may hold unique mechanisms of resistance and should allow for more personalized treatment. Abstract : Lung metastases have a high response rate to ipilimumab and anti–PD‐1 therapy, and their presence is associated with improved overall response and survival, whereas liver metastases have a lower response rate and are associated with inferior overall response and survival. Acquired resistance occurs in approximately 10% of all treated patients, and the overall survival rate at 1 year after progression is greater than 80%.